2019
DOI: 10.1021/acs.analchem.8b05486
|View full text |Cite
|
Sign up to set email alerts
|

Lucigenin-Tris(2-carboxyethyl)phosphine Chemiluminescence for Selective and Sensitive Detection of TCEP, Superoxide Dismutase, Mercury(II), and Dopamine

Abstract: Development of simple and effective chemiluminescence (CL) systems for multiple sensing applications is significantly important but still a challenge. Until now, the majority of CL systems primarily utilized hydrogen peroxide (H 2 O 2 ) as coreactant, which is limited in its stability and selectivity due to the easy decomposition of H 2 O 2 in the presence of several ions. In this study, we develop a new and intense CL system by combined use of tris(2-carboxyethyl)phosphine (TCEP), a highly solution stable and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Later, Nozaki et al (1996) developed and validated a new method for dopamine using chemiluminescence. This method attracted more and more attention because of its high sensitivity, simplicity and rapidity (Saqib et al, 2019). Additionally, Li et al (2000) reported a semi-automated method detection of L-dopa and dopamine in plasma by electrospray LC/MS.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Nozaki et al (1996) developed and validated a new method for dopamine using chemiluminescence. This method attracted more and more attention because of its high sensitivity, simplicity and rapidity (Saqib et al, 2019). Additionally, Li et al (2000) reported a semi-automated method detection of L-dopa and dopamine in plasma by electrospray LC/MS.…”
Section: Discussionmentioning
confidence: 99%
“…As of these sources, non-enzymatic options using phenazine methosulphate [206] , NADH and molecular oxygen or enzymatic reaction by xanthine dehydrogenase [207] could be named. After the superoxide anion radical is generated, wide range of detection techniques could be used for its detection, such as colorimetric, fluorescence, spectrophotometric and chemiluminescence [208] , [209] , [210] , [211] , [212] . As the chemical agent, 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) has the ability to trap superoxide anion and ESR can detect the resultant DMPO-OH adducts [213] .…”
Section: The Level Of Os and Related Compoundsmentioning
confidence: 99%
“…Compared with traditional detection techniques, CL has significant advantages, such as high sensitivity, wide linear range and simple measurement equipment. 1–4 In general, common CL systems include liquid phase CL, gas phase CL, solid phase CL and heterogeneous CL. 5–8 Compared with other three CL systems, liquid phase CL systems are much more uniform with high signal stability, simple and convenient operation.…”
Section: Introductionmentioning
confidence: 99%
“…Common liquid CL reagents include acridine hydride compounds, acridine ester compounds, peroxide oxalate compounds, bipyridine ruthenium compounds, potassium manganate and Ce( vi ). 2,9 Lucigenin is one of the most attractive CL compounds, 3 and has been widely used in enzyme immunoassay, 10 metal ion determination and hydrogen peroxide detection. 11 Most lucigenin CL systems need hydrogen peroxide as a coreactant.…”
Section: Introductionmentioning
confidence: 99%